Research Dominance Definitions May Not Identify Higher Risk Limb for Anterior Cruciate Ligament Injury in NCAA D3 Student-Athletes - Paul A. Cacolice; Brianna E. Starkey; Christopher R. Carcia; Paul E. Higgins (International Journal of Sports Physical Therapy)
# Background/Purpose